2022
DOI: 10.3389/fcell.2021.800529
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Modeling Mitochondrial Cardiomyopathy Using Human Induced Pluripotent Stem Cells

Abstract: Around one third of patients with mitochondrial disorders develop a kind of cardiomyopathy. In these cases, severity is quite variable ranging from asymptomatic status to severe manifestations including heart failure, arrhythmias, and sudden cardiac death. ATP is primarily generated in the mitochondrial respiratory chain via oxidative phosphorylation by utilizing fatty acids and carbohydrates. Genes in both the nuclear and the mitochondrial DNA encode components of this metabolic route and, although mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 166 publications
(197 reference statements)
0
5
0
Order By: Relevance
“…Prominent examples include the Barth syndrome (BTHS) and Friedreich’s ataxia syndrome (FRDA). An overall list of mtDNA and nucDNA genes contributing to mitochondrial function and corresponding mutations in a disease context have been extensively reported elsewhere ( El-Hattab and Scaglia, 2016 ; Barca et al, 2020 ; Pavez-Giani and Cyganek, 2021 ; Caudal et al, 2022 ). Since these syndromes are based on nuclear or mitochondrial gene mutations with a prominent cardiac phenotype, the iPSC-CM platform provides an excellent tool to study the underlying disease drivers.…”
Section: Insights Into Mitochondrial Cardiomyopathies Using Ipsc-cmmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples include the Barth syndrome (BTHS) and Friedreich’s ataxia syndrome (FRDA). An overall list of mtDNA and nucDNA genes contributing to mitochondrial function and corresponding mutations in a disease context have been extensively reported elsewhere ( El-Hattab and Scaglia, 2016 ; Barca et al, 2020 ; Pavez-Giani and Cyganek, 2021 ; Caudal et al, 2022 ). Since these syndromes are based on nuclear or mitochondrial gene mutations with a prominent cardiac phenotype, the iPSC-CM platform provides an excellent tool to study the underlying disease drivers.…”
Section: Insights Into Mitochondrial Cardiomyopathies Using Ipsc-cmmentioning
confidence: 99%
“…Mitochondrial dysfunction can arise as a primary cause due to a genetic mutation or as a secondary consequence ofan existing disease or other influences (environmental, toxins, etc.) ( Pavez-Giani and Cyganek, 2021 ). The mitochondrial genome (mtDNA) codes for 37 genes important for oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that iPSC-derived fibroblasts recapitulated the disease phenotype and did not demonstrate altered levels of heteroplasmy in culture and, therefore, represented a unique and novel model [ 47 , 48 ]; however, appropriate heteroplasmy levels, mitochondrial maturation, and mitochondrial respiratory functions should be considered. Moreover, significant progress has been made in developing efficient protocols for the directed differentiation of iPSCs into functional cardiomyocytes (iPSC-CMs); thus, we are now able to generate defined cardiac subtypes in large quantities and with high purity [ 59 ]. There is substantial evidence showing that iPSC-CMs with congenital cardiomyopathies represent the phenotype of the disease, such as abnormalities in cardiolipin processing, sarcomere assembly, myocardial contraction, ROS production, and cardiomyocytes functioning, and correlating with the abnormalities and cardiac dysfunction observed in patients [ 49 , 50 ].…”
Section: Disease Modeling For MCMmentioning
confidence: 99%
“…Then large animals are considered as the further step before clinical transition to measure specific cardiac electrophysiology. This approach can lead to the simulation of potential drug reactions in different organs throughout the body, although numerous failures have reminded researchers that interspecies differences may represent a barrier to fully transfer experimental test results to clinic practice ( Pavez-Giani and Cyganek, 2021 ; Bourque et al, 2022 ; Tricot et al, 2022 ). Then the human based clinical trial is critical to fully validate a newly invented drugs.…”
Section: Limitations To Drug Developmentmentioning
confidence: 99%
“…The interest in reprogramming cell fate has led to a revolutionary change in regenerative medicine, which achieves a “copy-paste” of patient-specific genotype cells from the bench to the bedside ( Carvajal-Vergara et al, 2010 ; Itzhaki et al, 2011 ; Yazawa et al, 2011 ; Kim et al, 2013 ). In the past decade, researchers in the field of hIPSC have attempted to solve a series of fundamental issues, including whether hIPSC have the ability to differentiate into different types of functional cells ( Ramalho-Santos, 2009 ; Maher, 2013 ; Zhao et al, 2019 ; Cowan et al, 2020 ; Lee et al, 2022 ); whether hIPSC-derived cells could mimic pathophysiological processes; and whether this completely “ in vitro ” model could help researchers unravel underlying pathogenetic mechanisms and provide clues on diagnostic and therapeutic choices ( Pavez-Giani and Cyganek, 2021 ; Faulkner-Jones et al, 2022 ; Yang et al, 2022 ). Along with their performance in several functional tests, hIPSC-derived cells show unique advantages, although even fully mature tissue characteristics still cannot be achieved today.…”
Section: Introductionmentioning
confidence: 99%